2007
DOI: 10.1128/jvi.02509-06
|View full text |Cite
|
Sign up to set email alerts
|

Lytic and Latent Antigens of the Human Gammaherpesviruses Kaposi's Sarcoma-Associated Herpesvirus and Epstein-Barr Virus Induce T-Cell Responses with Similar Functional Properties and Memory Phenotypes

Abstract: The cellular immunity against Kaposi's sarcoma-associated herpesvirus (KSHV) is poorly characterized and has not been compared to T-cell responses against other human herpesviruses. Here, novel and dominant targets of KSHV-specific cellular immunity are identified and compared to T cells specific for lytic and latent antigens in a second human gammaherpesvirus, Epstein-Barr virus. The data identify a novel HLA-B57-and HLA-B58-restricted epitope in the Orf57 protein and show consistently close parallels in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…T-cell responses to KSHV-encoded latent antigens and lytic antigens have been identified in both healthy immunocompetent donors and immunocompromised patients (32)(33)(34)(35)(36)(37). Although generally weak, KSHV-specific CD8 T cells responses are more frequent, diverse, and strong in asymptomatic KSHV-infected patients than Kaposi's sarcoma patients (38).…”
Section: Discussionmentioning
confidence: 98%
“…T-cell responses to KSHV-encoded latent antigens and lytic antigens have been identified in both healthy immunocompetent donors and immunocompromised patients (32)(33)(34)(35)(36)(37). Although generally weak, KSHV-specific CD8 T cells responses are more frequent, diverse, and strong in asymptomatic KSHV-infected patients than Kaposi's sarcoma patients (38).…”
Section: Discussionmentioning
confidence: 98%
“…33,34 These KSHV-specific responses were also lower than those reported in similar studies using individuals co-infected with HIV on HAART therapy, yet they showed a similar immunodominance profile with epitopes from LANA more frequently recognized than Kaposin. 9,10 These responses did seem more frequent than those described in HIVinfected donors with KS before HAART 2 or in transplant patients with KS before changing their immunosuppressive regime. 35 Because the ex vivo T-cell responses were weak, we generated T-cell clones for further study.…”
Section: Discussionmentioning
confidence: 70%
“…36 However, our findings show some contrast to what may be expected based on studies of ex vivo stimulation of donors' PBMCs with overlapping LANA peptides that resulted in stimulation of mostly CD8 Ï© T cells. 9 Furthermore, ex vivo stimulation of PBMCs with dendritic cells sensitized with overlapping LANA peptides has been shown to stimulate CD8 Ï© T-cell responses. 5 Using these LANA-specific CD4 Ï© clones to probe recognition of LANA-expressing cells, we found that EBV-transformed B cells, cells that have an intact class II antigen processing pathway, could efficiently process and present LANA antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 + T-lymphocytes are also important in controlling KSHV infection, but CD8 + T-lymphocyte epitopes are most frequently found in sera from HIV/KSHV-infected patients (Bihl et al, 2007;Brander et al, 2001;Robey et al, 2010).…”
Section: Immunologic Control Of Acute Infectionmentioning
confidence: 99%